2019
DOI: 10.25082/jpbr.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of carbopol with NVP for designing antibiotic drug loaded hydrogel dressings for better wound management

Abstract: In the present work an attempt has been made to design the antibiotic drug loaded carbopolpoly(NVP) based hydrogel wound dressings for better wound care. The polymer films were characterized by SEM-EDX, AFM, FTIR, 13 CNMR, TGA/DTA/DTG, DSC, and swelling studies. Besides drug release, various biomedical properties (viz. blood compatibility, mucoadhesion, oxygen permeability, water vapour transmission rate, microbial penetration, tensile strength, bursting strength, resilience, stress relaxation, and folding end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…Similarly, two endothermic peaks are indicated at 280 °C and 310 °C, respectively, followed by a phase glass transition. This indicates that developed hydrogels lead to thermal degradation in the range of 350–400 °C, although the thermal stability of the developed hydrogels exhibits better stability than the individual components [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, two endothermic peaks are indicated at 280 °C and 310 °C, respectively, followed by a phase glass transition. This indicates that developed hydrogels lead to thermal degradation in the range of 350–400 °C, although the thermal stability of the developed hydrogels exhibits better stability than the individual components [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure b,c shows the DSC thermograms of PAA, PAA/HA, and PAA/functionalized-HA hydrogels (HG) evaluated at pH = 7.4 and 4.1. All thermograms exhibit three characteristic regions ascribed to the following transitions: (A) water, melting transition, T m ; (B) water, evaporation transition, T e ; and (C) polymer, glass transition ( T g ). After deconvolution, the identified regions turned out to be the sum of several peaks representing different phase switches; thermodynamic parameters are summarized in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Conclusively, the discussion demonstrates that the fabricated network of microgel was thermally stable due to the cross-linking of its basic unreacted ingredients. B. Singh et al (2019) developed carbopol-based hydrogels and reported high thermal stability for fabricated hydrogels [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aliquot of 5 mL was taken after a regular interval of time and a medium of the same quantity was added back to maintain the sink condition constant throughout the dissolution experiment. The collected aliquots were analyzed on a UV-vis spectrophotometer (U-5100, 3J2-0014, Tokyo, Japan) at λ max 272 nm in triplicate [ 43 ]. In order to deduce the release mechanism of TP from ASPA-pAMPS microgels, zero order, first order, Korsmeyer–Peppas, and Higuchi kinetic models were applied for all formulations of the developed microgels [ 36 ].…”
Section: Methodsmentioning
confidence: 99%